Experimental study and mathematical modeling of viscoelastic dampers with wider temperature range based on blended rubber matrix. (1st July 2023) - Xu, Zhao-Dong; Yang, Yang; Zhu, Yi-Nan; Ge, Teng
Abstract: The glass transition temperature of existing viscoelastic (VE) materials is low, usually under 0 °C, thus the desired damping performance for VE dampers cannot be achieved at room temperature. On this issue, this study investigated the feasibility of utilizing blended rubber matrix to widen the working temperature range of VE materials, thereby improving the energy dissipation capacity at room temperature. A series of VE material samples based on blended rubber matrix were prepared, and the optimal formula was selected and applied in the fabrication of VE dampers. Then, the performance tests of VE dampers based on blended rubber matrix and single rubber matrix were conducted and compared. Results show that VE dampers based on blended rubber matrix have wider temperature range and better energy dissipation capacity than those based on single rubber matrix. A mathematical model for VE dampers based on blended rubber matrix was proposed by combining the internal variable theory and the temperature-frequency equivalence principle, and the accuracy of the proposed model was verified by comparisons between the calculated results and experimental data. Highlights: Different formulas of VE materials based on blended rubber matrix were prepared. The optimal formula has the effective damping temperature range of 78.3 °C, the loss factor of 1.98 and the glass transition temperature of 22.4 °C, achieving purpose to widen the effective working temperature range of VE materials. An internal variable mathematical model for VE dampers based on blended rubber matrix was proposed by combining the internal variable theory and temperature-frequency equivalence principle to account for the effects of displacement amplitude and temperature, respectively. The accuracy of this model was verified by the comparisons between the model calculated results and experimental data.